A review of the types of some Otostigmus (Parotostigmus) (Scolopendromorpha, Scolopendridae, Otostigminae) of the Andes mountain range - Chagas-Jr, Amazonas; Souza, Emerson Marques (Zootaxa, 2024)
Some species of the subgenus Parotostigmus Pocock, 1895 from South America are revised. Previously, 20 species and two subspecies of Parotostigmus were considered to be distributed throughout the Andes from Venezuela to Argentina, but after this study, thirteen species and one subspecies remain valid. Twelve types were examined (O. insignis Kraepelin, 1903, O. muticus Karsch, 1888, O. pococki Kraepelin, 1903, O. silvestrii Kraepelin, 1903, O. lavanus Chamberlin, 1957, O. mesethus Chamberlin, 1957, O. leior Chamberlin, 1955, O. parvior Chamberlin, 1957, O. volcanus Chamberlin, 1955, O. calcanus Chamberlin, 1944, O. amazonae Chamberlin, 1914 and O. bürgeri monsonus Chamberlin, 1957). O. lavanus syn. nov. is a junior synonym of O. insignis; O. parvior syn. nov. is a synonym of O. mesethus; O. amazonae syn. nov. and O. calcanus syn. nov. are synonyms of O. muticus, O. volcanus syn. nov. is a synonym of O. leior; and O. bürgeri monsonus syn. nov. is a synonym of Rhysida celeris (Humbert & Saussure, 1870). A lectotype and a paralectotype are here designated to O. mesethus. Two species, O. scabricauda (Humbert & Saussure, 1870) and O. rex Chamberlin, 1914, previously reported from Colombia, Peru and Brazil, were excluded from the Andean region.